Aesthetic restoration of posteror teeth. Proper creation of contact points: clinical case - A. V. Mitronin; A. Sh. Platonova; A. V. Gridasova; I. A. Ruzin (LLC "Endo Press", 2020)
Lesions of class II are the most common types of dental caries. The complexity of the diagnosis of contact lesions, the presence of a lot of nuances in the restoration of contact walls determines the high relevance of this issue today. A male patient, 21 years old came to dental clinic of Department of Cariesology and Endodontics MSUMD complaining on the pain on the right upper molars area, constant food partical jamming and unacceptable state of previous restorations. After the analysis of clinical situation and inspection was done the carious process was observed in the 24-27 tooth area. I decided to remove the old restorations, to restore the natural morphology of occlusal surfaces with using Ceram-X. Duo composite material and Palodent V3 matrix system.